Identifying differential benefits from a flipped-group pedagogy in introductory microeconomics. (January 2019) - Ficano, Carlena K. Cochi
Abstract: A growing literature documents the potential for benefits to be realized from non-traditional pedagogical approaches to teaching introductory economics at the undergraduate level. However, increased interest in and justification of the use of more engaged pedagogy that blends in class and online learning to reach a new and diverse generation of college students makes it imperative that we, as instructors, understand who is best served by such teaching innovations. In this paper, I present student outcome results from an informal post hoc experiment conducted over four semesters in which an Introductory Economics course is taught in its entirety three times over two semesters using traditional lecture methods and then three times over two subsequent semesters using a flipped-group pedagogy. In the latter, approximately 70% of class time is devoted to completion of graded in-class group assignments and the majority of content is delivered out of class through a series of publicly available videos. Results from the analysis indicate that in this particular context, the benefits of the flipped-grouped classroom pedagogy were not distributed equally. Specifically, while students with more developed math literacy and non-minority students benefited from the flipped pedagogy as evidenced by higher performance on the third semester exam and, to a lesser extent, on the averaged semester exams, the flipped format had a negative impact on weaker and minority students.